2021
DOI: 10.2478/johh-2021-0005
|View full text |Cite
|
Sign up to set email alerts
|

Hydrobiochemical balance of total mercury in a forest catchment area at former cinnabar mining locality

Abstract: We studied the hydrobiochemical balance of total mercury (THg) in a forest ecosystem covering an area affected by mining activity in the past (14th – 18th cent.) in the Kremnické vrchy Mts. (central Slovakia). A reference plot was located in an undisturbed area very close to primeval forest of Badínsky prales natural reserve. We analysed THg in bulk precipitation, throughfall, litterfall, forest floor percolate, forest soil and assimilatory organs of tree species. Results pointed out to high wet mercury deposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…It will be useful for determining the optimal distribution range of European beech under changing climate conditions in hydrological modelling. Mačejná et al (2021) hydro-bio-chemical balance of total mercury at former cinnabar mining locality. The most important fluxes of total mercury in two small forested catchment areas with different anthropogenic loads in the Kremnické vrchy Mountains.…”
Section: Catchment Scale Surface Subsurface and Groundwater Flow Proc...mentioning
confidence: 99%
“…It will be useful for determining the optimal distribution range of European beech under changing climate conditions in hydrological modelling. Mačejná et al (2021) hydro-bio-chemical balance of total mercury at former cinnabar mining locality. The most important fluxes of total mercury in two small forested catchment areas with different anthropogenic loads in the Kremnické vrchy Mountains.…”
Section: Catchment Scale Surface Subsurface and Groundwater Flow Proc...mentioning
confidence: 99%
“…Thus, the concentration of PM 2.5 particulate matter is to some extent determined by air pollution in the form of gaseous pollutants, hydrocarbons, metal ions (including heavy metals), and nanoparticles [13]. Fine particulate matter is often a source of dangerous heavy metals, such as lead, cadmium, and mercury [14]. Xu et al [15] reported that most particulate mercury (PHg) was concentrated in finer PM 2.5 particles.…”
Section: Introductionmentioning
confidence: 99%